2021
DOI: 10.1007/s10549-021-06170-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer treatment and survival differences in women in remote and socioeconomically disadvantaged areas, as demonstrated by linked data from New South Wales (NSW), Australia

Abstract: Introduction Reducing variations in cancer treatment and survival is a key aim of the NSW Cancer Plan. Variations in breast cancer treatment and survival in NSW by remoteness and socioeconomic status of residence were investigated to determine benchmarks. Reducing variations in cancer treatment and survival is a key aim of the NSW Cancer Plan. Variations in breast cancer treatment and survival in NSW by remoteness and socioeconomic status of residence were investigated to determine benchmarks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Some Australian studies of female breast cancer survival have reported no strong disparities in breast cancer survival between inner‐regional areas and urban areas 9,24,26,32 albeit in different Australian states. Yu et al 34 reported that for the most recent period covered in their study (2002–2005), after adjusting for SES (as well as age and stage of diagnosis), the estimated relative excess risk of breast cancer death for women living in inner‐regional areas compared with major city dwellers was 0.90, but this survival advantage was not statistically significant, albeit after adjusting for cancer stage.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some Australian studies of female breast cancer survival have reported no strong disparities in breast cancer survival between inner‐regional areas and urban areas 9,24,26,32 albeit in different Australian states. Yu et al 34 reported that for the most recent period covered in their study (2002–2005), after adjusting for SES (as well as age and stage of diagnosis), the estimated relative excess risk of breast cancer death for women living in inner‐regional areas compared with major city dwellers was 0.90, but this survival advantage was not statistically significant, albeit after adjusting for cancer stage.…”
Section: Discussionmentioning
confidence: 94%
“…There have been several Australian studies that have examined socio‐economic and rural–urban disparities in breast cancer mortality 29,30 . Some have examined socio‐economic disparities alone 7,31 rural–urban disparities alone 24,26 or both 8,9,32–34 . In most Australian studies that included a measure of cancer stage at initial diagnosis, the effect of stage on survival was either statistically controlled when estimating socio‐economic and rural–urban disparities 7–9,32,34 or it was used to stratify the sample, and then disparities were examined within stage 26 .…”
Section: Introductionmentioning
confidence: 99%
“…We note that the stratification of hospitals as high and low volume using the EUSOMA definition of 150 patients per year is not validated for the ANZ population, where a significant proportion of the population live in regional or geographically remote regions. In Australia, geographic remoteness is associated with higher rates of mastectomy, 23 reduced used of radiotherapy and less immediate breast reconstruction, but not lower survival 24 . In ANZ, a ‘low‐volume’ regional surgeon may participate in a ‘high‐volume’ metropolitan MDT and refer patients to metropolitan services.…”
Section: Discussionmentioning
confidence: 99%
“…and high-volume centre (HVH ≥150 patients p.a.). As per EUSOMA definition 90.9% (239) of centres were considered low-volume centres and 9.1% (24) were high-volume centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation